Trustworthy Autonomous Systems (TAS): The Verifiability Approach - Mousavi, Mohammad Reza (2022)
utonomous systems are taking over the decision-making in many crucial aspects of our lives. Trust in them will help users benefit from such systems without harming themselves. Establishing the right level of trust involves a holistic validation and verification process, accounting for aspects such as interactions with the physical world and human users. In this talk, I present our ongoing effort to provide a holistic framework for ensuring the veri-fiability of autonomous systems.